Genetic analysis for earliness under varying environments in chilli (Capsicum annum L.) - A V Agalodiya, D B Prajapati, (Journal of Spices and Aromatic Crops, 2012)
Six generations P1 P2 F1 F2 BC1 and BC2 of six families were developed in chilli (Capsicum annum L.) from 11 inbreds and were used to apply A, B, C and D scaling tests in the attributes of earliness viz., days to 50.0% flowering (DTF) and days to fruit ripening (DTFR) in different environments at Jagudan (Gujarat). The experiment was conducted in Kharif 2007 under high fertility condition (E1), Kharif 2007 under low fertility condition (E2) and Summer 2007 under high fertility condition (E3). For DTFR in Kharif, low fertility and summer grown conditions enhanced the expression of dominant/partially dominant genes. Whereas, DTF in low fertility as well as late sowing conditions depressed the expression of dominant/partially dominant genes. Detection of epistasis in a cross in one environment and not in the other emphasized the influence of environment on interaction parameters. High role of epistasis for ripening and flowering in all the three environments was observed. In general, for inheritance of days to flowering preponderance of dominance gene effects or due weightage of additive and dominance epistasis and dominance × dominance gene effects were noticed. For improvement of this trait, heterosis breeding was fruitful, where importance of non-additive gene effects with greater influence of dominance gene effects was estimated. The parents GVC–111, Junagadh Gholar, JCh–730 and JCh–725 contributed desirable genes for imparting earliness.